The Value of the Right to Vote - Stephan Tontrup; Rebecca Morton (SSRN, 2015)
We conducted a mixed lab and field experiment during a naturally occurring election. We offered subjects the opportunity to relinquish their voting rights for money. Significantly more participants refused to sell their rights than later participated in the election. Subjects were more willing to accept money for abstention from voting than for giving up the right to vote itself. In a second experiment we gave subjects an incentive to vote. Before and after the election we measured participants' knowledge about the parties' positions. Even though they would not have voted without the incentive, they improved their knowledge, suggesting that they value the vote. Our findings show that people derive strong utility from their democratic rights and status as a voter independently of participation. Based on the results we develop a new concept of rights utility and conclude that low turnout does not translate into democratic apathy and should not be used to justify quorum rules and restrict direct participatory rights.
Keywords: 330; Rights Utility; Valueing Voting Rights beyond their Participation Value